THE ROLE OF S-AMLODIPINE IN ARTERIAL HYPERTENSION THERAPY WITH COMBINATION OF CALCIUM CHANNEL BLOCKERS AND BETA-BLOCKERS - M. A. Maksimova; Yu. V. Lukina; S. Yu. Martsevich (Столичная издательская компания, 2015)
Aim. To study efficacy and safety of calcium channel blocker, S-amlodipine, in combination with β-blocker, atenolol, in patients with arterial hypertension (HT) 1-2 degree com- pared to fixed combination of racemic amlodipine and atenolol.Material and methods. Patients (n=31, 7 men and 24 women) with HT 1-2 degree were included into the study. The patients were randomized into two groups by the com- binations sequence. Treatment with each combination lasted 4 weeks. Office blood pressure (BP) was assessed at baseline and at the end of the treatment periods, possible side effects were registered.Results. All patients completed the study. Both combination of S-amlodipine+atenolol and fixed combination of racemic amlodipine+atenolol reduced systolic (in average, -15.9 and -12.7 mm Hg, respectively) and diastolic (in average, -7.3 and -5.3 mmHg, respectively) BP significantly. Heart rate also decreased during therapy (in average, -3 and -4 bt/min, respectively). The differences between combinations BP and heart rate effects were not significant. 8 and 16 adverse events were registered during S-amlodipine+atenolol and racemic amlodipine+atenolol therapies, respectively Conclusion. Combination of S-amlodipine+atenolol, as well as combination of racemic amlodipine+atenolol are effective in the treatment of patients with HT 1-2 degree, however combination with S-amlodipine has less number of adverse events.